A criança indígena nos estudos acadêmicos no Brasil: uma análise das produções científicas (2001 – 2012) - ARAÚJO, Sheila Alves de (Universidade Federal do Pará, 2014)
This paper examines the conceptions of Indigenous Childhood in academicians present studies produced in Brazil. Contributions to this study, it was considered as a guiding question: what conceptions of Childhood for the various indigenous ethnic groups in academic productions in Brazil in the period 2001-2012? The overall objective was to investigate the conceptions of childhood to the various indigenous ethnic groups present in academic productions in Brazil in the period 2001-2012, aimed (1) to identify and map these conceptions of indigenous children in different ethnic groups present in academic productions; (2) describe the process of education of indigenous children in several Brazilian indigenous ethnicities; (3) address the cultural practices of indigenous children mentioned in these studies; (4) discuss the relevance, progress and limits of such studies to the understanding of indigenous children in Brazil. The methodological path followed for the development of this study was bibliographical whose source Dissertations and Theses collected on the portal of CAPES in the period 2001-2012 on indigenous children. For the purpose of systematizing the corpus of analysis of this study and facilitate understanding of the material, the theses were organized into three themes: (1) ethnic conception of indigenous children; (2) cultural practices of indigenous children; (3) Indigenous education. From the choice of themes, it was thought in categories that could facilitate the understanding of the methodology chosen for this dissertation. Was then chosen for each thematic axis a category, namely: (1) Freedom; (2) Play; (3) Indigenous education (traditional school). Regarding the categories, it was possible to realize how important it was to mention them in this study because it allowed us to understand them well to bring out the rich arsenal that emerge when studying the conceptions of childhood linked to freedom, play and education. Such conceptions allowed us to have a new look about childhood in indigenous societies, from advances / limits. The results also showed that studies of childhood and / or indigenous child is incipient, particularly in the state of Pará and this is due to the fact that local researchers have not yet awakened the interest in the topic in question, and list some possible reasons for this "no interest": lack of motivation of researchers in this area, the inclusion of these studies in various areas of knowledge that are not necessarily in the field of education and poor access communities. We also noticed that the productions performed in our region on the theme Indigenous children are computed at the source of the researchers who come here to study it in leaving the North in the limit of production on indigenous children. Moreover, there is an urgent need to investigate the childhood and / or children living in the most diverse indigenous societies. Here is a challenge to be overcome and attempt to understand the child's world and your logical thinking to reality, learning as complex and full guy, so their perceptions of everyday village, school, family, rituals and symbols constitute themselves into a task of paramount importance.